2019
DOI: 10.1111/exd.13857
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes in chronic inflammatory skin diseases and skin tumors

Abstract: Exosomes are membrane vesicles of endocytic origin that can mediate communication between cells and the transport of cellular components such as microRNAs, mRNAs, proteins and DNA. Recently, exosomes have been under investigation for their significant roles in both healthy physiology and disease states. Herein, we review the role of exosomes in chronic inflammatory skin diseases and skin tumors, especially focusing on systemic lupus erythematosus, psoriasis, atopic dermatitis, bullous pemphigoid and melanoma. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 78 publications
0
36
0
1
Order By: Relevance
“…This study shows, for the first time, the presence of circulating exosomes in patients with psoriasis. Exosomes are involved in inflammatory processes, and their involvement in psoriasis has been suggested (6,7). A previous study (12) demonstrated phospholipase A2 activity within IFN-α-induced mast cell-derived exosomes, which could be transferred to CD1a-expressing target cells.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This study shows, for the first time, the presence of circulating exosomes in patients with psoriasis. Exosomes are involved in inflammatory processes, and their involvement in psoriasis has been suggested (6,7). A previous study (12) demonstrated phospholipase A2 activity within IFN-α-induced mast cell-derived exosomes, which could be transferred to CD1a-expressing target cells.…”
Section: Discussionmentioning
confidence: 98%
“…Although the field of exosome research in cancer progression is expanding, there are very few studies into the role of exosomes in immune-mediated inflammatory diseases (6,7). Psoriasis is a chronic, autoimmune skin disease associated with a T-helper-17 response induced by the release of IL-23 from myeloid epidermal dendritic cells, leading to proliferation of keratinocytes, resulting in psoriatic plaque formation (8).…”
mentioning
confidence: 99%
“…MiR-21 in MM cells is either synthesized intracellularly or transferred from the tissue environment by miR-21-enriched exosomes that recently gained high interest within the pathogenesis of various skin diseases including MM [ 96 , 97 ]. Exosomes are extracellular vesicles (EVs) of endocytic and secretory exocytic origin that mediate three-dimensional communication between cells.…”
Section: Exosome-mediated Mir-21 Transportmentioning
confidence: 99%
“…Although exosomes were initially thought of as cellular debris, they are now increasingly recognized as important mediators that regulate biological behaviors of cells . In recent years, exosomes have been considered promising biomarkers for diagnosis of various diseases and treatment monitoring in diabetic cardiomyopathy, rheumatoid arthritis, skin diseases, cancer, urinary tract infection, asthma pathology, and even orthopedic conditions . Moreover, study of the bioactivity of exosomes in cell cultures or in vivo has become popular in an effort to understand their physiological functions .…”
Section: Introductionmentioning
confidence: 99%